PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS CANVA DAN CAPCUT PADA MATERI STUKTUR BUMI UNTUK PESERTA DIDIK KELAS VIII SMP/MTS - Muna, Salma Nilna; Noer Af’idah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding of students on the abstract nature of the earth's structure material and the use of learning media process at school. These conditions have an impact on less than optimal student learning outcomes. This study aims to develop Canva and CapCut-based audio-visual learning media on the earth's structure material for grade VIII SMP/MTs students and determine the level of validity and practicality. This research is a development research with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The trial subjects were 21 grade VIII students. Data were collected through expert validation sheets and student response questionnaires, then analyzed using a Likert scale percentage. The results showed that the developed media obtained a validity level of 99.2% with a very valid category based on the assessment of material experts, media experts, and practitioners. The level of practicality based on the student response questionnaire reached 97.1% with a very practical category. Thus, Canva and CapCut-based audio-visual learning media on the earth's structure material are declared very valid and practical for use in science learning in junior high schools/Islamic junior high schools.